(untitled) (The University of Nairobi Journal of Language and Linguistics, 2023)
This paper is about the VOT characteristics of the six English plosive consonants as they are realised in the non-ethnically marked Kenyan English pronunciation. This is compared with the General British (GB)1 pronunciation. The data analysed in the paper was obtained from reading of the Boy Who Cried Wolf passage by a sample of 14 university lecturers, who served as speakers. Half of the sample was female and the other half male. The passage was phonemically transcribed using the Phonetizer* software. The output of transcription was further cross-checked using the Oxford Advanced Learner’s Dictionary. The pronunciation of four token words containing the six GB plosives occurring in syllable onset was analysed using Praat (a speech analysis software developed by Boersma & Weenink, 2016). Quantitative data on segment duration was analysed using the Statistical Package for Social Sciences (SPSS). The study found that the non-ethnically marked KenE pronunciation, unlike GB, typically does not aspirate voiceless plosives where they are expected to be aspirated, i.e. in initial stressed syllables, while it fully voices their voiced counterparts.